Theory of Truncation Resonances in Continuum Rod‐Based Phononic Crystals with Generally Asymmetric Unit Cells. Issue 2 (11th January 2023) - Al Ba'ba'a, Hasan B.; Willey, Carson L.; Chen, Vincent W.; Juhl, Abigail T.; Nouh, Mostafa
Abstract: Phononic crystals exhibit Bragg bandgaps, frequency regions within which wave propagation is forbidden. In solid continua, bandgaps are the outcome of destructive interferences resulting from periodically alternating material layers. Under certain conditions, natural frequencies emerge within these bandgaps in the form of high‐amplitude localized vibrations near a structural boundary, referred to as truncation resonances. In this paper, the vibrational spectrum of finite phononic crystals which take the form of a one‐dimensional rod is investigated and the factors that contribute to the origination of truncation resonances are explained. By identifying a unit cell symmetry parameter, a family of finite phononic rods, which share the same dispersion relation, yet distinct truncated forms, is defined. A transfer matrix method is utilized to derive closed‐form expressions of the characteristic equations governing the natural frequencies of the finite system and decipher the truncation resonances emerging across different boundary conditions. The analysis establishes concrete connections between the localized vibrations associated with a truncation resonance, boundary conditions, and the overall configuration of the truncated chain as dictated by unit cell choice. The study provides tools to predict, tune, and selectively design truncation resonances, to meet the demands of various applications that require and uniquely benefit from such truncation resonances. Abstract : Phononic crystals exhibit frequency regions within which wave propagation is forbidden (bandgaps). These are the outcome of destructive interferences resulting from periodically alternating material layers. Often, natural frequencies emerge within these bandgaps in the form of localized vibrations near the boundary, known as truncation resonances. Here, the fundamental factors that contribute to the origination of such truncation resonances are investigated.